PHYTOCHEMICAL ANALYSIS, LIQUID CHROMATOGRAPHY, AND MASS SPECTROSCOPY AND IN VITRO ANTICANCER ACTIVITY OF ANNONA SQUAMOSA SEEDS LINN. - Mehta, Shuchi Dave; Paliwal, Sarvesh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the present study is to evaluate in vitro anticancer property and phytochemical analysis using liquid chromatography and mass spectroscopy (LCMS) method of hydroalcoholic extract of seeds of Annona squamosa (AS) Linn. Seeds of AS Linn. are traditional medicine treating various diseases and have shown anticancer activity. Due to lack of survival benefit, cancer is a deadly global disease. Method: The anticancer activity was evaluated using the sulforhodamine B assay method on five cancer cell lines: Breast cancer cell line, cervix cancer cell line (SiHa), colon cancer cell line (HT)-29, liver cancer cell line, and ovary cancer cell line (Ovcar). The phytochemical analysis was performed using LCMS method. Result: The phytochemical characterization was done using LCMS method which showed 15 different molecular weight compounds. The extract showed an average in vitro anticancer activity at a concentration of 100 Î¼g/ml against all cancer cell lines. The best activity was observed against Ovcar-5 cell line (69.72) and was also significant against HT and SiHa cell lines. Conclusion: The phytochemical analysis showed the wide range of phenols and flavonoid which are showing potent anticancer activity of AS seeds.